Phenotypic predictors of pathogenic variants in probands with hypertrophic cardiomyopathy. (3rd October 2022) - Ranganathan, D; Killian, M K; Moore, D M; Gallagher, M G; McGorrian, C M C G; Galvin, J G
Abstract: Introduction: Hypertrophic cardiomyopathy (HCM) is the most common inherited cardiomyopathy (CM) and a leading cause of sudden cardiac death (SCD). With growing access to genetic testing, and incorporation of genetics in diagnosis and personalized management, it is critical to better understand the phenotypic predictors of pathogenic or likely pathogenic (P/LP) variants. This has implications for family screening, as well as resource planning. Aims: To identify the phenotypic predictors of genotype positivity in HCM patients (pts). Methods: In this retrospective single center study, 213 pts, who had undergone comprehensive HCM testing were assessed. Thirteen pts were excluded (6 – SCD, 7 – significant, non-HCM gene). Demographic information was obtained from clinic data and each patient's LVH pattern was then classified as sigmoid, concentric, reverse or apical based on trans-thoracic echocardiogram (TTE). Pathogenicity of variants was classified according to the American College of Medical Genetics (ACMG) criteria. Results: A total of 200 pts were included in the analysis, of which 167 had TTE undertaken in the study center, allowing for further detailed phenotype analysis. In the 200 pts, the mean age was 53.85 (SD 14.04) with 151 (75.5%) being male, 66 pts (17.5%) had an underlying diagnosis of hypertension (HTN) with an average of 1 anti-hypertensive agent (58.7%), 30 pts had a family history of SCD (17.5%), 41 pts (24.6%) had underlying atrial fibrillation, 53 pts had a history of ventricular arrhythmia (26.5%), 61 pts had an implantable defibrillator (31.8%), 3 pts had an aborted cardiac arrest (1.5%), 7 (3.5%) pts had septal myo-mectomy and 4 (1%) pts required a cardiac transplant. A core HCM panel (17 genes) was performed in 192 pts, 6 pts had extended HCM (69 genes) and 2 pts had global CM panel (109 genes), with a yield, of LP/P in 58 (30.2%), 3 (50%) and 1 (50%) within each respective panel. No gene, including likely benign (LB) and benign (B), was identified in 98 pts (49%). MYBPC3 and MYH7 were the most frequently identified variants and 50% of pts carried a risk factor in the FHOD3 gene (Graph 1). Sub-analysis of 167 pts with TTE showed the concentric pattern of LVH was most frequent at 31.5% (53 pts) followed by reverse, apical and sigmoid patterns. A LP/P Variant was identified in 7 (13.2%), 37 (88.1%), 4 (10.5%), 1 (2.9%) accordingly (Table 1). Younger pts, females, family history of SCD and non-HTN pts were more likely to have a LP/P variant identified. Mean IVSd, did not predict a LP/P variant identification, however low normal LVIDd and reverse LVH pattern did (p value <0.001). Conclusion: In our study assessing phenotype predictors of LP/P HCM genetic finding, younger pts, females, family history of SCD, normotensive and reverse LVH pattern on TTE positively correlated with LP/P variant identification. This study has implications for supporting better phenotype-based genetic counselling and resource usage for HCM pts. Funding Acknowledgement: Type of funding sources: None.